STUDENT TEACHERS’ DIGITAL LITERACY COMPETENCE AND PRACTICES IN “KAMPUS MENGAJAR” PROGRAM - Fauziah Fauziah (Epigram, 2025)
This study aims to explore student teachers’ digital literacy competence and practices during their participation in the Kampus Mengajar Program. This program offers the skills to apply the technologies for teaching and learning and create collaborative and interactive learning in preparing them to become a teacher. A qualitative case study design was employed in understanding student teachers perceive, develop, and apply digital literacy in real teaching contexts. The data was constructed through semi-structured interviews and photo documents with eight student teachers of Kampus Mengajar Program and analyzed using thematic analysis. The results show that student teachers perceive digital literacy as a crucial skill in addressing the challenges of education in the digital era. The Kampus Mengajar Program is perceived to significantly contribute to enhancing digital literacy skills through providing knowledge related to digital literacy and utilizing technology in learning. However, challenges remain in terms of limited school infrastructure, insufficient digital training, and difficulties in managing digital-based administrative tasks. The study highlights the importance of integrating digital literacy more explicitly into teacher education curricula and fostering institutional support to strengthen student teachers’ digital competence and pedagogical practices. Future research is suggested to investigate factors influencing digital literacy development and the impact of digital teaching practices on student learning outcomes.